PERILAKU PROFESIONAL TENAGA KESEHATAN PADA PELAYANAN KESEHATAN PRIMER PUSKESMAS SELAT PANJANG KABUPATEN KEPULAUAN MERANTI TAHUN 2013 - Asiyah Uswatun Nisa; Dedi Afandi; Suri Lesmana Dwi Lesmana (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
The professional behaviour of health-care workers is highly required in concession regions, especially in the coastal regions. This research aims for discovering the professional behaviour of health-care workers of Selat Panjang community health center (Puskesmas), Meranti Islands Regency that was assessed basing on the six elements of professional behaviour. The design of this research uses exploration method with qualitative approaches on nine health-care workers of Selat Panjang community health center (Puskesmas), Meranti Islands Regency, who selected by using snowball sampling method. Data collection was done by interview method and recorded with an audio recorder. The result of this study shows that all the respondents possess altruism, respect for others, honor and integrity, accountability, and duty. There are only some informants who possess excellence. In general, half of the Selat Panjang community health center (Puskesmas) health-care workers possess the elements of professional behaviour in carrying their duty, especially in providing service for the patients.Keyword: professional behaviour, altruism, respect for others, honor and integrity, accountability, excellence, and duty